ENIGMATIC INDUCTION OF CYTOMIXIS IN ALLIUM CEPA ROOT MERISTEM BY AGLAIA EDULIS ROXB. LEAF EXTRACT AND ITS PHYTOCHEMICAL RATIONALE - RAVINDRAN, ARCHANA ELAMKULAM; THOPPIL, JOHN ERNEST (Asian Journal of Pharmaceutical and Clinical Research, 2020)
Objective: The present study aims to analyze the potential of Aglaia edulis Roxb. leaf extract to induce cytological aberrations in Allium cepa root meristem and to determine the phytoconstituents in the extract. Methods: Cytotoxicity evaluation of the leaf methanolic extract was done using Allium cepa assay using various concentrations. Volatile phytoconstituents in the extract were determined using gas chromatography–mass spectrometry analysis. Results: Considerable number of cytomictic cells along with other aberrations was observed. The occurrence of cytomixis was found to be dose dependent where it ranged from 6.58±0.35 to 29.45±0.45. The percentage of cytomictic cells among the total aberrant cells was observed between 35.19±1.67 and 77.39±1.39. The phytochemical analysis of the plant extract revealed the presence of active secondary metabolites. Conclusion: The synergistic action of the active compounds might have triggered the phenomenon of cytomixis which, in turn, could be exploited for the production of polyploids.